The role of signals in two variations of differential‐reinforcement‐of‐low‐rate procedures. Issue 1 (3rd January 2018) - Becraft, Jessica L.; Borrero, John C.; Davis, Barbara J.; Mendres‐Smith, Amber E.; Castillo, Mariana I.
Abstract : Differential‐reinforcement‐of‐low‐rate (DRL) schedules are used to decrease the overall rate of, but not eliminate, a target response. Two variations of DRL, spaced‐responding and full‐session, exist. Preliminary comparative analyses suggest that the two schedules function differently when unsignaled. We compared response rates under these two DRL variations with and without signals. In Experiment 1, five preschool students played a game in which points were earned under DRL schedules. In some sessions, a stimulus signaled when responses would be reinforced (S+) or not reinforced (S‐). In others, only an S‐ was present. Signals (S+/S‐) facilitated and maintained responding in both types of DRL schedules. In Experiment 2, we modified the signals with five different preschoolers. Instead of an S‐ only, we did not present any signals. Elimination and high variability of the target response were observed with the S‐ only and absence of S+/S‐, respectively. Signaled DRL schedules are recommended for application.